THE TWELVE QUILOMBOS AS A RESISTANCE MOVEMENT IN THE LAGOS REGION, FROM THE OLD CABO FRIO TO THE 21ST CENTURY - Pierre de Cristo, Jean (Revista Gênero e Interdisciplinaridade, 2025)
This article aims to discuss the importance of the struggle and resistance of the quilombola communities that remained in the Lagos Region, in the State of Rio de Janeiro, from the introduction of human beings from the African diaspora as enslaved people to the formation of colonial and contemporary quilombos. Today, the Lagos Region has twelve quilombola communities that remain alive to continue the historical legacy of their ancestors, people who came as slaves from various countries on the African continent to produce labor in the former Cabo Frio in the 17th century.